Dynamics of a Unicycle-Type Wheeled Mobile Manipulator Robot - Varela-Aldás, José (2020)
Mathematical modeling is widely used in robotics to display behaviors and design control algorithms; the dynamic model of a robot describes the movements considering the action of internal and external forces of the system. This paper presents the dynamics of a unicycle mobile manipulator robot using the Euler-Lagrange proposal and conditioning the model to obtain the output velocities in the robot from the desired velocities. Additionally, the dynamic model is complemented by the identification of parameters using experimental data obtained from the AKASHA robot. The results present the signals applied in the identification, the values of the dynamic constants are found and the validation data which indicate a correct performance of the proposal are graphically shown. © 2020, Springer Nature Switzerland AG.